(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article is devoted to the problem of preparation and presentation of a significant amount of information for export, import and transit traffic. The “single window" procedure is indicated. Representing the practical application of the concept of taming information flows. The analysis of the main models of approaches to the creation of a “single window" is carried out. The GHS system. Benefits for the state from the introduction of a “single window". Benefits for trade.